Strategi Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Karyawan Pada PT. Mitra Lestari Bumi Abadi - Gres Enjelita Panjaitan; Iwan Asmadi; Tri Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The human resource management strategy carried out by PT. Mitra Lestari Bumi Abadi to improve employee performance. The purpose of this researcher is to identify Human Resource Management Strategies in Improving Employee Performance at PT. Jakarta's eternal earth conservation partner. This study uses a non-statistical quantitative analysis method with data collection methods through interviews with the leadership/HRD and employees of PT. Mitra Lestari Bumi Abadi Jakarta, as well as by conducting direct field observations and documentation. The results of the research show that PT. Mitra Lestari Bumi Abadi implements several effective human resource management strategies to improve employee performance, namely: Recruitment and selection to obtain employees according to company criteria, regular employee training and development to improve employee skills and knowledge in the field of work, performance evaluation good and regular basis to help identify employee strengths and weaknesses, Compensation and incentives to achieve better performance results, positive organizational culture that encourages collaboration, teamwork, and innovation. In conclusion, an effective human resource management strategy can help improve employee performance.